Affect and Low Back Pain: More to Consider Than the Influence of Negative Affect Alone. Issue 10 (October 2016) - Hassett, Afton L.; Goesling, Jenna; Mathur, Sunjay N.; Moser, Stephanie E.; Brummett, Chad M.; Sibille, Kimberly T.
Abstract : Objectives: Affect balance style, a measure of trait positive affect (PA) and negative affect (NA), is predictive of pain and functioning in fibromyalgia and healthy individuals. The purpose of this study was to evaluate the distribution of affect balance styles and the relationship between these styles and clinical factors in low back pain. Methods: In this cross-sectional study, patients with low back pain (N=443) completed questionnaires and were categorized as having 1 of 4 distinct affect balance styles: Healthy (high levels of PA and low levels of NA), Low (low PA/low NA), Reactive (high PA/high NA), and Depressive (low PA/high NA). Comparisons between groups were made in regard to pain, functioning, and psychiatric comorbidity. Results: High NA was observed in 63% (n=281), whereas low PA was present in 81% (n=359). We found that having a Depressive style was associated with greater pain severity, increased odds for comorbid fibromyalgia, and worse functioning compared with having a Healthy or Low style. Yet, those with a Low style were at increased risk for depression compared with a Healthy style, whereas patients with a Reactive style had similar levels of pain, functioning, and depression as those with a Healthy affective style. Conclusions: Our study revealed that there are important differences between trait affect balance styles in regard to pain, mood, and functioning in low back pain. Findings related to Reactive and Low affective styles suggest that relationships between affect, pain, and disability in low back pain extend beyond considering NA alone.